PERANAN AKUN INSTAGRAM @NSHMOUNTAINGOLD SEBAGAI MEDIA INFORMASI CLUB BASKET NSH MOUNTAIN GOLD - fauziah, Fauziah; Mantiri, Randi; Kamaruddin, Muhammad Junaid (PRoMEDIA, 2024)
Social media is another form of communication which aim to promulgate informations and to communicate with many people. Social media can be used to help it users to provide informations and make better interaction with other users. Instagram is one of the example of social media platform that is rapidly grow among other platforms and currently Instagram has a high level of popularity. In the world of sports, social media is mostly used as media to give informations. This research aims to find out the role of the Instagram account of NSH Mountain Gold basketball club as a media for basketball club information. This research uses qualitative method and also use an interactive analysis model, which follows the process of data collection, data reduction, data presentation and drawing conclusions. Based on research that has been carried out using the uses and gratification theory by researchers regarding "The Role of the @nshmountaingold Instagram Account as Information Media for the NSH Mountain Gold Basketball Club" the researcher can come to the conclusion that the role of @nshmountaingold Instagram account is as a media to share information of NSH Moutain Gold Basketball Club and can fulfill cognitive, affective, personal integration and social integration needs. In other hand, the need to release tension is not a need for followers of the Instagram account @nshmountaingold.Keywords: Role, Instagram, Media Information